Unique experiences in religious groups, in the US and China—a qualitative study - Mason, Karen; Hu, Yuan; Kim, Esther; Korver, David; Xia, Lisa; Coniglio, Nick (2018)
This qualitative inquiry examined the unique experiences of members in religious groups in the US and China to inductively derive a theory of what protects against suicide. Twenty-one non-religious group members (NRGMs), 21 religious group members (RGMs), and four from both types of groups completed interviews which were analyzed using inductive thematic analysis. Results suggest that while both NRGMs and RGMs convene around a shared common goal, the RGMs goal was to live a life of faith together. Both NRGMs and RGMs experienced community, but RGMs’ valued vulnerable sharing and prayer as vital to growing their faith. Results are most consistent with the theory that religion protects against suicide because it shapes beliefs which enable a suicidal person to resist suicidal thinking. RGMs from China reported limited resources including few mature, experienced people who can provide spiritual guidance.
Keywords: suicide prevention; moral objections to suicide; RELIGIOUS groups